The Habit of Congregational Dhuha Prayer to Form the Character of Students at MAS Plus Al Hidayah - Indra Al-Hakim; Ahmed Hisyam (CV. Mitkom Indotama, 2026)
The purpose of this research is how to get students used to performing congregational dhuha prayers at MAS Plus Al-Hidayah. Can congregational dhuha prayer improve the religious character of students at MAS Plus Al Hidayah? What are the supporting and inhibiting factors for the implementation of congregational dhuha prayers at MAS Plus Al Hidayah. This research method is a qualitative method using informants through interviews. The results of this study show how to get students used to performing congregational dhuha prayers at MAS Plus Al Hidayah by making congregational dhuha prayers a rule that students must obey every morning. Congregational dhuha prayer can improve the religious character of students at MAS Plus Al Hidayah. The increase in religious character can be seen from the increase in learning discipline and increased compliance with school regulations as well as the increase in learning activities and the improvement of students' morals. The supporting factor for the implementation of congregational dhuha prayers at MAS Plus Al Hidayah is the good cooperation in its implementation between the principal and teachers and the availability of congregational dhuha prayer facilities. Pay attention to the inhibiting factors, namely there are still students who arrive late and there are still those who do not bring prayer equipment